Pengaruh Kompetensi dan Pengembangan Karir Terhadap Kepuasan Kerja di Pabrik Gula Tjoekir Jombang - Siti Sanidatur Rohmah (BIMA : Journal of Business and Innovation Management, 2020)
This study aims to analyze the effect of competence and career development on employee job satisfaction in the Tjoekir Jombang Sugar Factory by using quantitative data analysis research techniques and causal research methods with data through surveys and distributing questionnaires to 136 Tjoekir Jombang Sugar Factory employees using random sampling sampling, namely taking sample members from the population taken randomly without regard to strata that exist in that population. Data analysis techniques using Multiple Linear Regression. The results of testing this hypothesis show the results that: (1) competence has a partially significant effect on employee performance in the Sugar Factory, (2) career development has a partial effect on the performance of employees in the Tjoekir Jombng Sugar Factory and (3) Job Satisfaction and Career Development have an effect on simultaneous performance of employees at the Tjoekir Jombang Sugar Factory.